Case Report: PRRT in a patient with Zollinger-Ellison syndrome. The management of gastrointestinal complications - Di Franco, Martina; Durmo, Rexhep; Di Paolo, Maria Liberata; Giacosa, Roberto; Bannò, Elisa; Ambrosini, Valentina; Filice, Angelina (Frontiers in Oncology, 2025)
Zollinger-Ellison Syndrome (ZES) is a rare condition characterized by excessive gastric acid secretion due to gastrin-producing neuroendocrine tumors. Peptide Receptor Radionuclide Therapy (PRRT) with [177Lu]Lutetium Oxodotreotide is an effective treatment for advanced neuroendocrine tumors, including those associated with ZES. However, the gastrointestinal toxicity induced by ZES can complicate the administration of PRRT. We present a case of a patient with metastatic G2 neuroendocrine tumor of the duodenum and ampulla of Vater who experienced severe gastrointestinal complications after the first PRRT cycle due to exacerbated ZES. The implementation of a prophylactic treatment with high-dose proton pump inhibitors before and after the subsequent PRRT cycles allowed for the successful completion of the therapy. This case highlights the importance of considering ZES-related complications in patients undergoing PRRT. Proactive management with high dose acid-suppressing therapy can significantly improve patient tolerance and treatment outcomes. Further research is needed to optimize the management of ZES patients undergoing PRRT.